INTEGRATED ELEMENTARY SCHOOL EDUCATION IS AN IMPORTANT PREREQUISITE FOR FORMING A STUDENT’S CREATIVE PERSONALITY - Харковенко, Татьяна (Modern engineering and innovative technologies, 2019)
In this work the integrated approach is examined in the studies of junior schoolchildren. The state standard of primary general education is envisage one of the most important tasks of school is all-round development of child, his talents, capabilities, к